Film reboots - Herbert, Daniel, 1974-; Verevis, Constantine (Screen serialities, 2020)
Through a set of vibrant case studies, this collection investigates rebooting as a practice that seeks to remake an entire film series or franchise, with ambitions that are at once respectful and revisionary.